Reward : (MacMillan, 1998)
This book contains a presentation of the course design, methodological principles, and detailed teaching notes. There are four photocopiable tests. The teaching notes for each lesson, a discussion of some of the difficulties the learners may encounter, and more detailed methodological issues arising from the material presented.